O pensar como ‘objeto’ da filosofia e seu ensino em Hegel - Barrére Martin, Luiz Fernando (Revista Eletrônica Estudos Hegelianos, 2019)
The present essay aims to approach the crucial issue of the specificity of the philosophical activity and of its relation with knowledge in the philosophy of Hegel. Moreover, the need to justify its legitimacy within the domain of the other sciences is a requirement made in modern age to philosophy. Along with this general aim and in close relation with it, I will deal more specifically with Hegelian considerations about the teaching of philosophy. In order to do so, the text is divided in two principal moments: in the first, I will analyze the philosophical conception of Hegel and how the writing on the Difference presents a continuity with the way in which the question will be treated in the Encyclopaedia of 1830; in the second, Hegel's position on the teaching of this discipline will be analyzed, and in this case I will have in view Hegel's methodological texts of the period in which he was director and professor of Gymnasium in Nuremberg.